ABTPé: A Testament of Growth and Excellence in Foot and Ankle Surgery - Oliveira Junior , Antônio Alício Moreira de (Journal of the Foot & Ankle, 2024)
Our growth is undeniable! The evolution of the Brazilian Association of Medicine and Surgery of the Ankle and Foot (ABTPé) over the past few years is a testament to this. We have revamped the criteria for resident training, regulated, valued, and qualified training services, embraced the digital era, and made continuing education accessible online. The addition of thematic courses in the annual continuing education calendar has enriched our events, providing a platform to delve into the nuances that set specialists apart. We have also been fortunate to benefit from the expertise of our members, including Nicola Maffulli, Jonathan Deland, Tim Schepers, and others, who have shared their unique perspectives and experiences with us. With all these advances, we have also seen the growth of our publications in the best journals in the specialty, the development of new surgical techniques, the creation of international partnerships with colleagues of great relevance, and what began as a club in the pioneering days of foot and ankle surgery has evolved into a dynamic, ever-evolving society, with multiple leaders and reference services spread throughout the country. We cannot overlook the Brazilian Congress of Foot and Ankle Surgery as a significant chapter in our society’s evolution. This robust event draws massive participation from our specialists and esteemed international guests, showcasing diverse perspectives. Our strong partnership with the industry also plays a crucial role, as symposia and exhibition stands introduce new solutions, trends, and designs of fixation devices. Building this new space for publications and disseminating the experience of foot and ankle surgery in Latin America and worldwide was a courageous decision by the ABTPé, supported by the efforts of those who voluntarily dedicated themselves to editing, selecting, and disseminating the submitted papers. The authors publish more relevant information with each edition, translated into original articles, technical tips, and reviews. Yes, we are capable, and our efforts have put us on a path of success and growth that is irreversible. Our commitment to high-level foot and ankle surgery is unwavering and is evident at every meeting, course, and congress. Our journal, a reflection of this dedication, is no exception. It serves as a testament to our growth and competence in the field. Enjoy ABTPé; enjoy our Journal of Foot and Ankle.